Metal Complex of Some Conjugated 1,3-Diketones - Paul, Mathew; Krishnankutty, K. (Asian Journal of Chemistry, 2010)
Four new conjugated 1,3-diketones and their Cu(II), Ni(II) and Co(II) chelates of ML2 composition have been synthesized and characterized. The electronic, ir, 1H nmr and mass spectral data of the compounds are discussed.